Guía metodológica de voz sobre IP para la escuela de tecnologías de la Universidad de las Américas - Segovia Olivo, Erika Paola (2013)
Voice communication is essential when performing any activity whether personal or business level. Today people and businesses are dependent on this type of communication via fixed telephone networks or cellular. However in recent years has become popular for communicating other options such as Skype and Facebook that make use of the Internet data network especially for voice transmission. There are other solutions that have gone further and allow the coexistence of IP networks with conventional networks to exchange voice traffic through the inclusion of an element called IP core, which acts as a gateway between these networks….